Limb remote ischemic postconditioning protects integrity of the blood-brain barrier after stroke - Juan Li (Neural Regeneration Research, 2018)
Integrity of the blood-brain barrier structure is essential for maintaining the internal environment of the brain. Development of cerebral infarction and brain edema is strongly associated with blood-brain barrier leakage. Therefore, studies have suggested that protecting the blood-brain barrier may be an effective method for treating acute stroke. To examine this possibility, stroke model rats were established by middle cerebral artery occlusion and reperfusion. Remote ischemic postconditioning was immediately induced by three cycles of 10-minute ischemia/10-minute reperfusion of bilateral hind limbs at the beginning of middle cerebral artery occlusion reperfusion. Neurological function of rat models was evaluated using Zea Longa’s method. Permeability of the blood-brain barrier was assessed by Evans blue leakage. Infarct volume and brain edema were evaluated using 2,3,5-triphenyltetrazolium chloride staining. Expression of matrix metalloproteinase-9 and claudin-5 mRNA was determined by real-time quantitative reverse transcription-polymerase chain reaction. Expression of matrix metalloproteinase-9 and claudin-5 protein was measured by western blot assay. The number of matrix metalloproteinase-9- and claudin-5-positive cells was analyzed using immunohistochemistry. Our results showed that remote ischemic postconditioning alleviated disruption of the blood-brain barrier, reduced infarct volume and edema, decreased expression of matrix metalloproteinase-9 mRNA and protein and the number of positive cells, increased expression of claudin-5 mRNA and protein and the number of positive cells, and remarkably improved neurological function. These findings confirm that by suppressing expression of matrix metalloproteinase-9 and claudin-5 induced by acute ischemia/reperfusion, remote ischemic postconditioning reduces blood-brain barrier injury, mitigates ischemic injury, and exerts protective effects on the brain.